A modal approach for impact sound insulation measurement at low frequency. Issue 2 (June 2016) - Prato, Andrea; Schiavi, Alessandro; Ruatta, Anna
In typical laboratory volumes (40–80 m 3 ) and at low frequencies (50–100 Hz), the acoustic field is non-diffuse due to the presence of room modes. Under such conditions, standard sound insulation measurements and descriptors are not adequate to correctly characterize the insulating property of flooring systems, as far as the real perception of annoyance due to modes is concerned. In this article, a new approach focused on room modes, the so-called modal approach, is investigated. New descriptors for the evaluation of modal impact noise and the improvement of modal impact sound insulation along with a new measurement procedure are introduced. In particular, it is shown that results agree with the theoretical curve of structural transmissibility for floating floors. In the future, it will be necessary to introduce normalization terms in order to get repeatable and reproducible values and to improve the uncertainty budget assessment.